Virtual connections: a multidisciplinary study on behavior in social networks - Echavarría, Yisel Ramírez; Castillo, Verenice Sánchez; Gallego, Tulio Andrés Clavijo (AWARI, 2023)
This article investigates the impact of social networks on various aspects of contemporary society through a multidisciplinary approach. A theoretical review with a mixed approach was used which, after an evaluation of relevance, led to the identification of 21 articles that make up the research. Exploring the relationship between patterns of social network use and their effect on mental health, it is found that active interaction promotes psychological well-being, while passive consumption is linked to negative feelings such as loneliness and envy. In addition, we examine how these platforms influence identity formation and public opinion, highlighting their role in creating "echo chambers" that can intensify social polarization. It is also noted that while social networks enhance global connectivity, they can compromise the quality of interpersonal relationships. Nevertheless, they facilitate the formation of communities of support and solidarity, particularly in groups with common interests, contributing to community cohesion. This study underlines the duality of social networks as spaces of opportunity and challenge, highlighting the need for a conscious use to foster individual well-being and social cohesion.